Building Maintenance Processes and Practices The Case of a Fast Developing Country - Olanrewaju, Abdul Lateef; Abdul-Aziz, Abdul-Rashid.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
This book is designed to be an inclusive for the best practice approach to building maintenance management, where the processes, procedures and operational systems meet a high standard of professional and academic competence. It offers a different perspective on building maintenance management by presenting the schematic building maintenance value chain model and it’s implementation in Malaysian university buildings. The findings show an improvement to building performance, lower maintenance cost, building sustainability and increased maintenance service user satisfaction. The learning outcomes and summaries provided for each chapter and the extensive use of tables and figures add to the readability of the text. Though the book is based on data from Malaysia, it is useful for a much wider audience, and the informal writing style makes it an interesting reference source. This book is valuable for readers who are practitioners, professionals and for academic institutions that offer courses in the building field, including architecture, quantity surveying, civil engineering, building and facility management, property management, real estate. It will also be of interest to governments and others involved in the construction industry.   .
Overview -- An Overview of the Construction Industry -- Maintenance of Academic Buildings -- Malaysian Education System and University Buildings -- Building Maintenance Processes, Principles, Procedures, Practices and Strategies -- Methodological Issues -- Sustainability Maintenance Initiatives -- Conclusions and Recommendations.
Keywords: Building repair; Buildings—Repair and reconstruction; Energy efficiency; Buildings; Building Repair and Maintenance; Energy Efficiency; Building Types and Functions